Analisis Penerapan Budaya Sekolah 5S (Senyum, Salam Sapa, Sopan, Santun) Dalam Membangun Karakter di Sekolah Dasar - Gampang Saiful Hada; Erna, Erna Zumrotun (Universitas Ngudi Waluyo, 2024)
This research is based on the urgency of strengthening the 5S school culture (Smile, Greeting, Greeting, Polite and Courtesy) as a concrete step to strengthen student character in schools. Essentially, school culture is a reflection of moral and ethical values in building a humanist, personalized, and cultured educational climate as mandated by the main objectives of education in elementary schools. The 5S School Culture as core values becomes the basis of students' personalities in carrying out noble values that are familiarized at school. Therefore, the internalization of Smile, Greeting, Greeting, Polite and Courtesy is the basis for building student character that must be grown from an early age, especially in elementary school education, one of which is at SD Negeri 3 Sekuro. Based on this, this study aims to understand and analyze how the 5S culture is applied in the school environment in shaping student character and creating a positive learning environment. This research uses qualitative methods with descriptive research design. The results of this study indicate that the 5s school culture provides a basis and systematic guidance in realizing students with character and noble character as a representative of the personality of good elementary school students. Through continuity in familiarizing the 5 S culture (Smile, Greeting, Greeting, Polite, Polite), it will gradually form an educational climate with personality and culture as one of the strategic instruments that contribute to realizing the education of students. Abstrak Penelitian ini didasarkan pada urgensi penguatan budaya sekolah 5S (Senyum, Salam, Sapa, Sopan dan Santun) sebagai langkah konkret penguatan karakter siswa di Sekolah. Esensinya bahwa, budaya sekolah menjadi cerminan nilai moral dan etika dalam membangun iklim Pendidikan yang humanis, berkepribadian, dan berbudaya sebagai amanat tujuan utama Pendidikan di Sekolah Dasar. Budaya Sekolah 5S sebagai core values menjadi dasar kepribadian siswa dalam menjalankan nilai-nilai luhur yang di biasakan di Sekolah. Oleh karena itu internalisasi Senyum, Salam, Sapa, Sopan dan Santun adalah dasar membangun karakter siswa yang harus ditumbuhkan sedari dini, terlebih di Pendidikan sekolah dasar, salah satunya di SD Negeri 3 Sekuro. Berdasarkan hal tersebut, Penelitian ini bertujuan untuk memahami dan menganalisis bagaimana budaya 5S diterapkan di lingkungan sekolah dalam membentuk karakter siswa dan menciptakan lingkungan belajar yang positif. Penelitian ini menggunakan metode kualitatif dengan design penelitan deskriptif. Hasil Penelitian ini menunjukkan bahwa budaya sekolah 5S memberikan dasar dan panduan sistematis dalam mewujudkan siswa yang berkarakter dan berbudi pekerti luhur sebagai representative kepribadian siswa Sekolah Dasar yang baik. Melalui kontinuitas dalam membiasakan budaya 5S (Senyum, Salam, Sapa, Sopan, Santun), secara berangsur akan membentuk iklim Pendidikan yang berkepribadian dan berbudaya sebagai salah satu instrument strategis yang berkontibusi dalam mewujudkan Pendidikan berkulitas di SD Negeri 3 Sekuro Jepara.